The neuropsychology of starvation: set-shifting and central coherence in a fasted nonclinical sample. - Sarah Pender; Sam J Gilbert; Lucy Serpell (PLoS ONE, 2014)
OBJECTIVES: Recent research suggests certain neuropsychological deficits occur in anorexia nervosa (AN). The role of starvation in these deficits remains unclear. Studies of individuals without AN can elucidate our understanding of the effect of short-term starvation on neuropsychological performance. METHODS: Using a within-subjects repeated measures design, 60 healthy female participants were tested once after fasting for 18 hours, and once when satiated. Measures included two tasks to measure central coherence and a set-shifting task. RESULTS: Fasting exacerbated set-shifting difficulties on a rule-change task. Fasting was associated with stronger local and impaired global processing, indicating weaker central coherence. CONCLUSIONS: Models of AN that propose a central role for set-shifting difficulties or weak central coherence should also consider the impact of short-term fasting on these processes.